Dual purpose cows supplemented with nacedero (Trichanthera gigantea) in continuous grazing (Revista Sistemas de Producción Agroecológicos, 2016)
This research was conducted in the "Limoncitos" farm located in the Villavicencio city Cocuy village, which is dedicated to the exploitation of cattle breeding whose main source of food is Brachiaria decumbens grass, and in some cases the animals are supplemented with concentrated or Trichantera gigantea. For this work crossed cow Zebu x Brown Swiss and Zebu x Holstein in second and third lactation with an average production of 5.2 kg/cow/day and an average weight of 351.8 ± 15 kg, which were distributed in two groups as follows: T1 = grazing on B. decumbens grass, T2 = grazing more 9 kg/animal/day of T. gigantea in fresh matter. It was also supplied mineralized water and salt at will. The variables evaluated were: daily milk production, and weight of cows at the beginning and end of the experiment; the nutritional analysis and ruminal degradability of forages that were used were performed in the animal nutrition laboratory of UNILLANOS, also was determined fat and protein content in the milk. The T. gigantea acceptance by the cows was high, about 80%; the group was supplemented with this tree got better the production in one kg, while the witness maintained his steady production, therefore is observed a difference (P
Keywords: bovines; forage trees; ruminal degradability